2017
DOI: 10.1080/23337931.2017.1326009
|View full text |Cite
|
Sign up to set email alerts
|

Water sorption and solubility of polyamide denture base materials

Abstract: Purpose: Some patients experience adverse reactions to poly(methyl methacrylate)-based (PMMA) dentures. Polyamide (PA) as an alternative to PMMA has, however, not been well documented with regard to water sorption and water solubility. The aim of this in vitro study was to measure water sorption and water solubility of two PA materials compared with PMMA, and to evaluate the major components released from the PA materials and the effect on hardness of the materials. Methods: Ten discs (40.0 mm diameter, 2.0 mm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 20 publications
2
21
0
1
Order By: Relevance
“…Nonetheless, it should be noted that in some studies RPD performances, such as those related to masticatory efficiency, have been evaluated even after 5 or 6 months, suggesting that 1 year postevaluation can already provide some useful information . In addition, mechanical properties of VALPLAST and PMMA can change even earlier (within 8 weeks), due to water sorption and solubility, as reported by Nguyen and coworkers . Another limitation is that no data on bone loss in edentulous segments were reported.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Nonetheless, it should be noted that in some studies RPD performances, such as those related to masticatory efficiency, have been evaluated even after 5 or 6 months, suggesting that 1 year postevaluation can already provide some useful information . In addition, mechanical properties of VALPLAST and PMMA can change even earlier (within 8 weeks), due to water sorption and solubility, as reported by Nguyen and coworkers . Another limitation is that no data on bone loss in edentulous segments were reported.…”
Section: Discussionmentioning
confidence: 98%
“…Nonetheless, it was also found that VALPLAST‐RPD was characterized by increased difficulty in prosthesis care and roughness perceived by the tongue. Polyamide material is subjected to faster degradation and lower wear resistance as compared to PMMA and CoCR . This may also contribute to increased damage of the surface when cleaning, also causing the roughness of prosthesis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations